Corrosion properties of high silicon iron-based alloys in nitric acid - LI Ju-cang; WANG Shu-ying; ZHAO Ai-min (China Foundry, 2007)
The effect of copper and rare-earth elements on corrosion behavior of high silicon iron-based alloys in nitric acid was studied by means of static and loading current corrosion experiments. The anodic polarization curve was also made to discuss the corrosion mechanism. The examination on alloy microstructure and SEM corrosion pattern showed that when silicon content reached 14.5%, the Fe3Si phase appeared and the primary structure of the iron-base alloy was ferrite. When adding 4.57% copper in the iron alloy, its corrosion resistance in static diluted sulfuric acid was improved while its corrosion resistance and electrochemical corrosion properties in the nitric acid were decreased. In contrast, the addition of rare earth elements could improve the corrosion properties in all above conditions including in static diluted sulfuric acid and in nitric acid.